2021
DOI: 10.1002/app.51470
|View full text |Cite
|
Sign up to set email alerts
|

Effect of crump rubber on the solid particle erosion response of epoxy composites

Abstract: Present investigation characterizes solid particle erosion response of neat epoxy and crump rubber filled epoxy composites. Three types of composites were prepared by reinforcing crump rubber particles (10, 20 and 30 vol.%) in epoxy matrix. Neat epoxy samples were also prepared for comparison. Thermo gravimetric analysis revealed crump rubber composites have higher stability as compared with neat epoxy specimen. Differential scanning calorimeter tests reveal higher glass transition temperature for crump rubber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 59 publications
0
7
0
2
Order By: Relevance
“…The reinforcement of chemically treated sisal/hemp fillers which are usually elastic in behavior, improves the hardness of the specimen gradually when compared with untreated samples, as observed in Table 3. The lower hardness of SUBE56, HUBE56, and SHUBE56 composites may be advantageous in incrementing the resistance from erosion of specimens 143 . The shore hardness of the KSCBE56, KHCBE56, and KSHCBE56 composites was enhanced because of the homogeneous distribution of the sisal‐hemp fillers in the bio epoxy matrix by reinforcing suitable fillers and solid interfacial bonding within the Kevlar fabric, sisal‐hemp fillers, and polymer matrix.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reinforcement of chemically treated sisal/hemp fillers which are usually elastic in behavior, improves the hardness of the specimen gradually when compared with untreated samples, as observed in Table 3. The lower hardness of SUBE56, HUBE56, and SHUBE56 composites may be advantageous in incrementing the resistance from erosion of specimens 143 . The shore hardness of the KSCBE56, KHCBE56, and KSHCBE56 composites was enhanced because of the homogeneous distribution of the sisal‐hemp fillers in the bio epoxy matrix by reinforcing suitable fillers and solid interfacial bonding within the Kevlar fabric, sisal‐hemp fillers, and polymer matrix.…”
Section: Resultsmentioning
confidence: 99%
“…The lower hardness of SUBE56, HUBE56, and SHUBE56 composites may be advantageous in incrementing the resistance from erosion of specimens. 143 The shore hardness of the KSCBE56, KHCBE56, and KSHCBE56 composites was enhanced because of the homogeneous distribution of the sisal-hemp fillers in the bio epoxy matrix by reinforcing suitable fillers and solid interfacial bonding within the Kevlar fabric, sisal-hemp fillers, and polymer matrix. The highest shore hardness for the specimen without sisal-hemp fillers (KFBE56), whereas the lowest quantity was ascribed to the KSHUFBE56 sample.…”
Section: Shore D Hardnessmentioning
confidence: 99%
“…These trends are attributed to the ability of crump rubber particles to effectively absorb the heat during sliding wear. Thermogravimetric analysis curves reported in [42] reveal that all crump rubber-epoxy composites reveal a one-step degradation mechanism, and onset of degradation for EC-10, EC-20, and EC-30 takes place at 359, 362, and 365 °C, respectively. Furthermore, we also found that EC-30 registers a higher final degradation…”
Section: Disc Temperaturementioning
confidence: 93%
“…Numerous studies have indicated that elastomers are capable of absorbing the impact energy of erosive particles, and exhibit excellent erosion resistance under certain conditions. [34][35][36] In this study, a thermal deicing nanocomposite lm with solid particle erosion performance was fabricated using a highly elastic material, thermoplastic polyurethane (TPU), as the matrix, through a simple "spray-hot pressing" method. The composite lm has a sandwich structure that can uniformly distribute the ller and reinforce the structure.…”
Section: Introductionmentioning
confidence: 99%